Cross‐sectional associations between cortical thickness and independent gait domains in older adults. Issue 9 (5th May 2022) - Wang, Yingzhe; Jiang, Yanfeng; Lu, Heyang; Tian, Weizhong; Li, Peixi; Xu, Kelin; Fan, Min; Zhao, Xiaolan; Dong, Qiang; Jin, Li; Chen, Jinhua; Cui, Mei; et al.
Abstract: Background: Although the prevalence of gait disturbance is increasing with population aging, our understanding of its underlying neural basis is still limited. The precise brain regions linked to specific gait domains have not been well defined. In this study, we aim to investigate the associations of cortical thickness and different gait domains, and to explore whether these associations could be explained by cerebral small vessel disease. Methods: A total of 707 community‐dwelling participants from the Taizhou Imaging Study (mean age: 60.2 ± 3.0 years, 57.4% female) were involved. All participants underwent brain MRI and gait assessment. We obtained quantitative gait parameters using wearable devices and then summarized them into three independent gait domains through factor analysis. Cortical thickness was analyzed and visualized using FreeSurfer and Surfstat. Results: Three independent domains (pace, rhythm, and variability) were summarized from 12 gait parameters. Among gait domains, poorer pace was associated with the thinner cortical thickness of multiple regions, which included areas related with motor function (e.g., the primary motor cortex, premotor cortex, and supplementary motor area), sensory function (e.g., the postcentral gyrus and paracentral lobule), visuospatial attention (e.g., the lateral occipital cortex and lingual gyrus), and identification and cognition (e.g., the fusiform gyrus and entorhinal cortex). Such a relationship was only slightly attenuated after adjustment for cerebrovascular risk factors and cerebral small vessel disease. No statistically significant association was found between cortical thickness and the rhythm or variability domains. Conclusions: Poorer pace is independently associated with thinner cortical thickness in areas important for motor, sensory, cognitive function, and visuospatial attention. Our study emphasizes the importance of cortical thickness in gait control and adds value in investigating neural mechanisms of gait.